KAJIAN YURIDIS TERHADAP TINDAK PIDANA PORNOGRAFI MELALUI MEDIA SOSIAL - Dadin Eka Saputra (Al-Adl : Jurnal Hukum, 2017)
Technological advances the longer growing rapidly, including the rise of the use of social media and social networking. The goverment has been working hard to eradicate pornography. Pornography has damaged the values of morality f Indonesian society, especially young people. Through Act Law Number 44 Year 2008 About Pornography and The Law Number 11 Year 2008 of Information and Electronic Transaction as amended by Act Law Number 19 Year 2016 has arrenged abaout the criminal offence of pornography, however in this legisation there are still some weaknesses so often happens multitafsir in analyzing the formulation of rules relating to the determination of its criminal elements. This of course can affect law enforcement efforts on pornography, without exception on the criminal liability of acts of pornography.